Implementation of Character Education in Family to Stimulate the Social Development of Early Childhood in Tanjung Batu Seberang Village - Tanzila, Siti Ade Ilma; Helmi, Henny; Nurrizalia, Mega (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the implementation of character education in families in stimulating the social development of early childhood in Tanjung Batu Seberang Village. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through interviews, observations, and documentation of parents of children aged 3-6 years. The results of the study indicate that families have an important role in instilling character values such as religious, honesty, tolerance, communicative, and social care. However, the implementation of these values is still not optimal, especially in the values of honesty, tolerance, and social care. In addition, six main methods were found in character education, namely role models, habituation, storytelling, advice, attention, and rewards and punishments. The role model and habituation methods are quite dominant methods, but have not been fully carried out consistently by parents. Based on these findings, it is recommended that parents increase their involvement and consistency in children's character education, as well as support from the village government through parenting counseling and training programs.